The cloaking of power : Montesquieu, Blackstone, and the rise of judicial activism - Carrese, Paul (University of Chicago Press, 2003)
How did the U.S. judiciary become so powerful-powerful enough that state and federal judges vied to decide a presidential election? What does this prominence mean for the law, constitutionalism, and liberal democracy both in America and internationally?In The Cloaking of Power, Paul O. Carrese provides a provocative and original analysis of the intellectual sources of today's powerful judiciary, arguing that Montesquieu, in his Spirit of the Laws, first articulated a new conception of the separation of powers and of strong but subtle courts.